Construction of 3D printable Pickering emulsion gels using complexes of fiber polysaccharide-protein extracted from Haematococcus pluvialis residues and gelatin for fat replacer - Wang, Mengwei; Yin, Zihao; Zeng, Mingyong (Food hydrocolloids, 2023)
Structural fat replacers that can meet the requirements of various forms of reduced-fat foods are essential for the application of fat replacement, and emulsion gels emerge as a potential alternative for fat replacers. In this study, fiber polysaccharide-protein extracted from Haematococcus pluvialis residues (FPHRs) formed FPHRs-Gelatin complexes with gelatin. Fourier transformed infrared spectroscopy confirmed the formation of hydrogen bonds between FPHRs and gelatin, the secondary structure order of the protein was enhanced. Three-phase contact angle determination showed that the contact angle of FPHRs-Gelatin complexes was 104°–114°. By exploring the effect of FPHRs concentration, gelatin concentration, and oil-water ratio on the emulsion gels, the Pickering emulsion gels were formed when the FPHRs and gelatin concentration were 2 wt% and 3 wt%, respectively. What's more, these emulsion gels had shear thinning phenomenon, low frequency dependence as well as excellent thixotropy when the oil-water ratio was 0.6, which indicated that they had strong structural support and great recovery capacity to be used as 3D printed materials. The 3D objects printed by the FPHRs-Gelatin complexes emulsion gels had superior print resolution and shape fidelity. This study provides a new type of emulsion gel with structure that can be used as an ideal fat replacer in food processing, the construction of a new 3D emulsion gel material is of great significance for broadening the applications of gelatin-based gels and microalgal food. [Display omitted] •Fiber polysaccharide-protein formed complexes with gelatin.•The complexes can form oil-in-water emulsion gels useful for 3D printing.•Emulsion gels had strong structural support and great recovery capacity.•This study provides a new idea for the customization of fat replacer.•Broadening the applications of gelatin-based gels and microalgal food.